RELASI SAINS, BUDAYA, DAN AGAMA UPAYA PENDEKATAN PARADIGMA YANG MENYATUKAN - Jayana, Thoriq Aziz (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2018)
This paper attempts to provide a way out of disintegration between science, culture and religion. Where all three must look for a formulation so as to form harmonization and integration that is well established after the occurrence of distinctions which causes serious 'friction' in the three domains. From here the beginning of classifying two kinds of knowledge, namely al-ulum ad-diniyah and al-ulum ad-dunyawiyah (which includes science and culture). By finding a relationship that uses a dialogic-integrative paradigm, it will become a bridge that connects the points of equality of the three domains.